INNOVATIONS IN RURAL TOURISM IN POLAND AND ROMANIA - Sin, Alexandru; Nowak, Czeslaw; Bogusz, Malgorzata; Kowalska, Magdalena; Janigová, Emília (Economics of Agriculture, 2020)
The interest in rural tourism in Poland and Romania is the result of processes originating from economic and social factors reflecting the needs of both rural inhabitants and tourists. A significant growth in the field of rural tourism leads to implementation of innovative products in the development of tourist services. The aim of the study presented in this paper is to show the essence of innovation as a component of the contemporary tourist industry, and to present the type of innovations that occur in rural tourism in Poland and in Romania. The theoretical part analyses innovation in the field of rural tourism. The empirical part, in turn, presents case studies of tourist businesses in rural areas, taking into account the implemented innovations, in both Poland and Romania. The case studies are presented based on interviews with owners of tourist facilities.